Informational Asymmetry Between Informed and Retail Investors While Investing in the Indian IPO Market - R., Deepak; Gowda, Swathi (Indian Journal of Finance, 2014)
Do retail investors make investment decisions in the primary markets based on personal decisions (mainly gut feeling) ? by taking clues from institutional investors ? or by seeking help of ratings given by credit-rating agencies ? - these are the common questions about retail investors investing in primary markets. Primary markets give a lot of opportunities to retail investors to purchase stocks at lower rates considering the future prospects of the companies. Underpricing of the IPOs and market efficiency play a crucial role in the primary markets as suggested by asymmetric information models. The true value of a share is determined by many factors, which are considered in various proportions to assess the demand in the market. The book building process, adopted throughout the world, helps in identifying the strength of the value of a share, but still, in many ways, to a researcher, finding the true value of a share is an art and not an absolute science. The study aimed at understanding the decision making capabilities of the retail investors based on the information available to them. The study mainly examines how and why information asymmetry exists between the informed and retail investors and whether the winner’s curse exists in the Indian stock markets. A sample of 177 IPOs were considered for the study, with the time period of the study being from 2008-12. Stepwise regression analysis, correlation, and Granger’s causality tests were conducted. The study found conclusive evidence to support asymmetric behavioural theories. The study revealed that retail investors took clues from institutional investors before investing in the primary markets, but they did not conduct any market research, nor did they consider credit ratings as an important component before entering the primary markets.